Mikroalga Divisi Bacillariophyta yang Ditemukan di Danau Aur Kabupaten Musi Rawas - Harmoko Harmoko; Yuni Krisnawati (Jurnal Biologi Universitas Andalas, 2018)
Lake Aur has many aquatic biota as well as become one of the mainstay attractions in Musi Rawas Regency. Community activities and lack of awareness of tourists on the cleanliness and importance of maintaining the lake environment have an impact on water pollution. One of the organisms that can be used as an indicator of river water quality is microalgae. The purpose of this study is to determine the types of microalgae Bacillariophyta divisions that exist in the lake Aur, Musi Rawas.The type of research used is survey research. Bacillariophyta Division consists of two classes, 6 orders, 7 families, 8 genera and 11 species. Observed environmental factors: temperature: 290C, pH: 6.7, Brightness: 115 cm and dissolved oxygen amount of: 38 mg / L. Based on the results of research and discussion, we can conclude that: the type of microalgae division bacillariophyta were found in Lake Aur namely: Cylotella sp, Eunotia sp, Eunotia pectinalis, Fragilaria croronensis, Synedra acus, Nitzschia sp, Nitzschia acicularis, Surirella sp, Surirella elegans, Pinnularia sp and Stauroneis sp.